Prototype evaluation of a novel selective leverage gear system - Tiau, See Ping (2020)
A new concept of gear train is proposed, namely the selective leverage gear system. It is a unique primary gear system with levers, guided by an oblong to transmit force from the power source in selective ways. Currently, no commercial product has existed on the proposed gear system and modelling. The aim of this study is to investigate the kinematics and evaluate static and dynamic behaviour of the leverage gear train so that recommendations can be made for further developing work. The model was compared with the experimental results of static using digital torque meter and for dynamic torques Arduino with FSR approach is applied. For static analysis, results showed a lower error distribution at position before 20°. Results showed that the dynamic output torque was not as expected, which resulted in limitation to test speed at 30, 60, and 90rpm, but 30 and 90rpm came out with more precise results. It was observed that the speed of the device was also limited by the lubrication and material properties of the gears as well as the effects of load. These particular limitations may influence research findings, but have not been focused in this initial study and should be considered for future analytical and experimental work. Finally, conclude that prototype increase output torque.